2020
DOI: 10.2147/rrtm.s269936
|View full text |Cite
|
Sign up to set email alerts
|

<p>Off-Label Use of Chloroquine and Hydroxychloroquine for COVID-19 Treatment in Africa Against WHO Recommendation</p>

Abstract: COVID-19 is continuing as a big challenge for the globe and several types of research are continued to find safe and effective treatment and preventive options. Although there is a lack of conclusive evidence of their benefit, there is worldwide controversy to use anti-malarial drugs, hydroxychloroquine and chloroquine, for the treatment of COVID-19. FDA issued an emergency use authorization to the use of these drugs for the treatment of COVID-19. On the contrary to the FDA, the European Medicines Agency has w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…The results revealed that there is no significant improvement in these patients within 15 days ( Cavalcanti et al, 2020 ). Although the World Health Organization (WHO) recommends against using these drugs due to the limited evidence, most African countries are still utilizing them as the routine COVID-19 treatment ( Belayneh, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that there is no significant improvement in these patients within 15 days ( Cavalcanti et al, 2020 ). Although the World Health Organization (WHO) recommends against using these drugs due to the limited evidence, most African countries are still utilizing them as the routine COVID-19 treatment ( Belayneh, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, misinformation ( Arshad et al, 2020 ), the lack of other treatment, combined with the severity of the illness, and a desire to try all avenues have led to several settings continuing to use these drugs. For example, in many African countries, despite WHO recommendations, hydroxychloroquine, chloroquine, and azithromycin were still being advised for use in the summer of 2020 and may be still being used off-label ( Abena et al, 2020 ; Belayneh, 2020 ). In India, it appears to still be guidance to use hydroxychloroquine as a prophylactic for ‘healthcare workers’ ( National Taskforce for COVID-19, India, 2020 ).…”
Section: Covid-19 Impact On Amrmentioning
confidence: 99%
“…Even though there is a clear lack of adequate evidence of benefit of the drugs, many African and other countries have endorsed hydroxychloroquine repurposed (off-label) use for the treatment of COVID-19 contrary to the WHO recommendations [ 179 ]. On the other hand, the US Food and Drug Administration have also issued an Emergency Use Authorization for the use of chloroquine and hydroxychloroquine for the treatment of Covid-19 in adult populations [ 180 ].…”
Section: Drugs That Act On Microorganismsmentioning
confidence: 99%